EXPLORING THE BENEFITS OF CURRICULUM DEVELOPMENT FOR STUDENTS - Nursaputri, Esamada Rose; Aisyah, Siti (Abjadia : International Journal of Education, 2024)
The purpose of this study is to elucidate the meaning of curricular development and the advantages it offers to students. The advantages of curricular development, particularly for students, will be the subject of a literature study by the author. It is anticipated that the findings of this study will significantly affect pupils. It is hoped that in the future, the academic community will take the many advantages of curricular modifications seriously and fully, provided they are informed about them and understand their obvious benefits. so that the beneficial effects can be felt. The experimental studies and literature reviews published online by authorized publications with a DOI serve as the source of the data. These journals were acquired from a number of sources, including Google Scholar, Taylor & Francis, Research Gate, and others. 30 open access journals were chosen in this study so that the entire texts could be evaluated. The results of a review of several works of literature revealed three main themes of the benefits of curriculum development for students. These include relevance and real-world application, students’ needs and interest fulfillment, and enhancement of critical thinking and problem-solving skills